The affective interval. An investigation of the peaks and valleys during high- and moderate-intensity interval exercise in regular exercisers - Box, A. G.; Feito, Y.; Zenko, Z.; Petruzzello, S. J. (Psychology of Sport and Exercise, 2020)
Evidence supports the notion that people generally feel worse during high(er) intensity exercise but experience an affective rebound immediately following cessation that often exceeds pre-exercise feeling states. Considering rest/recovery is an integral part of interval exercise, it is of interest to determine the degree of affective reactivity and recovery that may occur during interval exercise of different intensities. The purpose of the present study was to examine affective reactivity to and recovery from an acute bout of moderate-intensity (MIIE) and high-intensity interval exercise (HIIE). Participants (N = 25, 13 females, 23.3 ± 4.0 yrs, BMI = 25.7 ± 4.1 kg m-2) completed 4 sessions at the same time of day with at least 24-h between each session: a baseline session to record resting affect, a graded exercise test on a stationary bike (cycle ramp protocol 25 W·min-1) to volitional exhaustion, and then completed a high- (HIIE) and moderate-intensity interval exercise (MIIE) session where affect was recorded prior to, during, and up to 30-min post exercise. Participants reported more negative feeling states during the HIIE session compared to the MIIE session, but these states recovered similarly as early as 5-min post-exercise. In addition, while affective change (reactivity and rebounds) were relatively equal during the MIIE, declines in affect during the HIIE outweighed the affective rebounds associated with rest, resulting in a large decline in affective state from pre-exercise.